PENGOLAHAN SAMPAH BOTOL PLASTIK DAN SAMPAH RUMAH TANGGA DENGAN METODE BIOPOT/BIOPORI DI DUSUN MONGGANG, PENDOWOHARJO, SEWON, BANTUL, D.I YOGYAKARTA - Anis Safety; Taufik Choirohman; Indriastuti Indriastuti; Korinta Azhar; Anggita Dewi Kusumastuti; Agus Kharmayana Rubaya; Ibnu Rois (JPS : Jurnal Pengabdian Serulingmas, 2022)
Conventional waste management that has been applied by the community has not been able to produce an appropriate solution, as evidenced by the volume of waste that has not been managed properly. This service activity is focused on socializing the processing of plastic bottle waste and household waste using the biopot/biopori method. This service was carried out in Monggang Hamlet, Sewon District, Bantul Regency, Yogyakarta Special Region Province in January 2022. The purpose of this service is to provide knowledge and its application to the community on how to process plastic bottle waste and household waste through the biopot/biopori system and improve community interest in processing household waste that is generated every day. To achieve these objectives, field survey, communication, counseling and socialization methods were used with the activity stages consisting of planning, implementation, and evaluation. The counseling event was attended by RT 36 social gathering participants consisting of RT heads, housewives and also attended by the head of Monggang Hamlet. Furthermore, socialization about waste is carried out and assisting activities in making biopots/biopori. This counseling was categorized as successful with almost all participants present very enthusiastic in the activity of making biopots/biopori. The process of this activity invites interest from the community because in terms of benefits, this activity is suitable and easy to implement in the environment.